Pengaruh Motivasi Kerja, Kepuasan Kerja, dan Komitmen Organisasi Terhadap Kinerja Pegawai Melalui Disiplin Kerja Sebagai Mediator - Yeni Dwi Hastuti; Tabrani; Roberto Akyuwen (Forum Kerjasama Pendidikan Tinggi, 2022)
The employee’s performance is the very important for the goal achievement on an organization. The purpose of this study was to examine and analyze the effect of work motivation, job satisfaction, and organizational commitment on employee performance through work discipline as a mediator at the Tegal City Diskominfo. This research method uses a quantitative research approach. The analysis process with a sample of direct observation with 49 respondents. The instruments used in this study using questionnaires. The questionnaire has been tested for validity and reliability. The research analysis uses Structural Equation Modeling (SEM). Based on the results of the analysis, it can be concluded that work motivation, job satisfaction, and organizational commitment has a significant and positive effect on employee work discipline. Furthermore, work discipline has a significant and positive effect on employee performance. While work motivation and job satisfaction have no effect on employee performance. The organizational commitment is known to have a significant and positive effect on employee performance.